Flagellar Hook Protein FlgE Induces Microvascular Hyperpermeability via Ectopic ATP Synthase β on Endothelial Surface - Li, Yuanyuan; Shen, Ying; Zheng, Yudan; Ji, Shundong; Wang, Mengru; Wang, Beibei; Han, Qingzhen; Tian, Yufeng; Wang, Yiqiang (Frontiers in Cellular and Infection Microbiology, 2021)
We previously demonstrated the immunostimulatory efficacy of Pseudomonas aeruginosa flagellar hook protein FlgE onto epithelial cells, presumably via ectopic ATP synthases or subunits ATP5B on cell membranes. Here by using recombinant wild-type FlgE, mutant FlgE (FlgEM, bearing mutations on two postulated critical epitopes B and F) and a FlgE analog in Pull-down assay, western blot, flow cytometry and ELISA assay, actual bindings of FlgE proteins or epitope B/F peptides with ATP5B were all confirmed. Upon treatment with FlgE proteins, human umbilical vascular endothelial cells (HUVECs) and SV40-immortalized murine vascular endothelial cells manifested decreased proliferation, migration, tube formation, surface ATP production and increased apoptosis. FlgE proteins increased the permeability of HUVECs monolayers to soluble large molecules like dextran as well as to neutrophils. Immunofluorescence showed that FlgE induced clustering and conjugation of F-actin in HUVECs. In Balb/c-nude mice bearing transplanted solid tumors, FlgE proteins induced a microvascular hyperpermeability in pinna, lungs, tumor mass and abdominal cavity. All effects observed in FlgE proteins were partially or completely impaired in FlgEM proteins, or blocked by pretreatment with anti-ATP5B antibodies. Upon co-culture of bacteria with HUVECs, FlgE were detectable in membrane and cytosol of HUVECs. It was concluded that FlgE posed a pathogenic ligand of ectopic ATP5B that, upon FlgE-ATP5B coupling on endothelial cells, modulated properties and increased permeability of endothelial layers both in vitro and in vivo. The FlgE-ectopic ATP5B duo might contribute to the pathogenesis of disorders associated with bacterial infection or ectopic ATP5B-positive cells.